2021
DOI: 10.1021/acs.jpcc.1c08138
|View full text |Cite
|
Sign up to set email alerts
|

QM/MM Studies on Thermally Activated Delayed Fluorescence of a Dicopper Complex in the Solid State

Abstract: Dicopper complexes with thermally activated delayed fluorescence (TADF) phenomena are important in enriching the arsenal of organic light-emitting diodes materials. However, the TADF mechanism is still elusive, especially in the solid state. Herein, we chose a TADF dicopper complex and investigated its geometric and electronic structures and absorption and emission spectra using DFT, TD-DFT, and QM/MM methods. On the basis of these results, we further estimate the fluorescence emission rate from the S 1 state,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Thus, K nr is found to be sensitive to the temperature, which is consistent with the previous research. 26 These results indicate that the excited state properties are associated with thermal motions. Furthermore, molecular conformation induces changes in excited state properties is investigated, and corresponding emission wavelengths, energies and decay rates are calculated and listed in Tables S3 and S4 (ESI †).…”
Section: Excited State Dynamicsmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, K nr is found to be sensitive to the temperature, which is consistent with the previous research. 26 These results indicate that the excited state properties are associated with thermal motions. Furthermore, molecular conformation induces changes in excited state properties is investigated, and corresponding emission wavelengths, energies and decay rates are calculated and listed in Tables S3 and S4 (ESI †).…”
Section: Excited State Dynamicsmentioning
confidence: 84%
“…Both the abovementioned methods and applications can be found in the studies by Shuai, Peng, and Cui and our work. [23][24][25][26][27][28][29][30][31][32]…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…The time interval for integration in eq is 1.0 × 10 –4 ps with a total 3 ps integral time to ensure these results converged. All ISC and rISC rates including Huang–Rhys factors and reorganization energies were calculated by our own developed code. , More details can be found in previous works. ,, …”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Recently, George group reported a PmDI-based CzPhPmDI emitter and observed TADF in PMMA films; however, its luminescence mechanism is still unclear, and it is questionable whether highly excited states are involved in the TADF. In addition, previous theoretical calculation works are usually carried out in crystal environments, ,, and thin film environments are scarcely reported. Inspired by this, we use the QM/MM method to model CzPhPmDI in PMMA film environments.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous mechanism investigations support experimental luminescence phenomena and predict the properties of TADF molecules. [31][32][33][34][35][36][37][38][39][40][41][42][43] For example, the Shuai group investigated the TADF mechanism of 1,2,3,5-tetrakis(carbazol-9-yl)-4,6-dicyanobenzene and found that the rotation of the Cz ligand between two cyano groups leads to the interconversion between S 1 and T 1 . The intramolecular steric hindrance hinders the nonradiative transition of S 1 -S 0 , which in turn enhances the fluorescence.…”
Section: Introductionmentioning
confidence: 99%